P-6-4p=-7p+6

Simple and best practice solution for P-6-4p=-7p+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P-6-4p=-7p+6 equation:



-6-4P=-7P+6
We move all terms to the left:
-6-4P-(-7P+6)=0
We get rid of parentheses
-4P+7P-6-6=0
We add all the numbers together, and all the variables
3P-12=0
We move all terms containing P to the left, all other terms to the right
3P=12
P=12/3
P=4

See similar equations:

| -3a-5-3a=-17 | | 2(5x+5)=-42+22 | | 1-4m+m+10=m+3-8 | | -9(n+10)=-162 | | 3x-12+2x+25=68 | | 3a-5-3a=-17 | | 5(x+2)-8(3x+5)=-49 | | 9-x=x+15 | | 12=5a+2-a | | 38​c−2=32​c−12 | | -6=n/10-7 | | -15-r=6-8r | | 2(2x+8)=-29+39 | | 144-7x+4x^2=0 | | 32+u−211=78. | | 7w-18=-5(w-6) | | 3x÷4+4=10 | | 3x+8-5x=2-x+2x-3 | | 180-x=70+180-x | | Y=2x^2+5(3x+2x) | | 20=x/(-6) | | 7n+4=-59 | | 10(-1+n)=70 | | -3(v-7)=-6v+24 | | 12/15=x | | 4t^2-13t-10=0 | | 2/3x-7/2x=3/4x-17 | | -5v+3(v-6)=-24 | | -8r=64. | | -54=3(k-1) | | x/(-23)=-2 | | 3(x=6)+5(8x+6)=48 |

Equations solver categories